Efeitos de um programa de prevenção de problemas de comportamento em crianças pré-escolares de famílias de baixa renda. - Rios, Karyne de Souza Augusto (2006)
The objective of this research was assess the effects of an early intervention program to low-income families living in a small city of São Paulo, to prevent the development of problems behavior in pre-school children, by the improvement of parental educational skills that are associated to pro-social behavior development (positive supervision and moral behavior) and the reduction of parental educational skills that are associated to problems behavior development (physical and psychological abuse, negligence, relaxed discipline, inconsistent punishment and negative supervision). Two parents group made part of the study. Each group should be constituted by six couple of parents (monoparental families or just one parent were accepted) and their respective children with ages between 6 months and 3 years old. But just four mothers in group A and one mother in group B (M5) had participated effectively. Parent interview, Parenting Sense of Competence Scale, Parenting Scale, Child Abuse Potential Inventory, Temperament Assessment Questionnaire and Client Satisfaction Questionnaire were applied with participants. Furthermore, observations of mother-child interaction were carried with one mother on group A and M5. The intervention consisted in ten weekly sessions that have dealt the following subjects: child development, parental skills communication, positive discipline management, domestic violence, positive parental supervision and moral behavior. The strategies that have been used were: videos, dynamics, discussions, role-play, relaxing technique, angry management, solving problems, homework, and others. The data obtained by interview were categorized to aim a social demographic analysis of the participants. Comparations between total scores of each measure before intervention, after intervention and in Follow-up were made. The observation of mother-child interaction, that was a sequential measure were registered in a table and have been categorized in comparative graphics between the groups. The results showed that all participants were living in a high risk context to problems behavior development in children. The Temperament Assessment Questionnaire indicated that all children have demonstrated styles of temperament that are related with problems behavior development. About the Parenting Sense of Competence Scale, one mother have increased their parental satisfaction and effectiveness score, two mothers only have increased their parental satisfaction score e two other mothers have reduced their parental satisfaction and effectiveness score. There were decreased of inconsistent discipline (laxness), overreactivity and verbosity using for all participants. The observation s data indicated more frequency of positive interactions between mothers and children and the increased of positive parental behavior after the intervention. Future studies are necessary to investigate intervention s process and to promote relations with other professionals and with the Government to get better results and long-term consequences to families and their children.